Diabetes mellitus as a Potential Risk Factor for Renal Disease among Nepalese: A Hospital Based Case Control Study - Mittal, Ankush; Sathian, Brijesh; Kumar, Arun; Chandrasekharan, Nishida; Sunka, Aditya (Nepal Journal of Epidemiology, 2010)
Background Diabetes mellitus is a well recognized public health concern and projections of its future effect are alarming. It is one of the leading causes of end stage renal disease in both developed and emerging nations. The objective of the present study was to assess the progressive deterioration of renal function in Diabetes mellitus among Nepalese. Materials and Methods It was a hospital based case control study carried out in the Department of Biochemistry of Manipal Teaching Hospital, Pokhara, Nepal between 1st January 2010 and 31st August 2010. The variables collected were age, gender, random blood glucose, serum urea and creatinine levels of the patients. Results Out of 440 patients, there was a slight predominance of males (54.1%) as compared to females (45.8%). Patients in between 41-100 years were 2.8 times more at risk of developing kidney disease as compared to age group (0-40 years)(Odds Ratio=2.8, p=0.0001). Diabetic patients were twice at risk of developing kidney disease than non diabetics (Odds Ratio=1.97, p=0.001). There was a significant increase in mean values of serum creatinine (CI 4.3 to 4.8) and urea (CI 118.55 to 153.50) in kidney disease patients with Diabetes mellitus. In non diabetic kidney disease patients, mean values of serum creatinine (CI 3.29 to 3.70) and urea (CI 98.88 to 116.92) were also moderately raised as compared to controls. Conclusion Diabetic renal lesions are not only preventable but also reversible. In summary, glycemic control significantly influences the rate of progression from microalbuminuria to proteinuria and from overt nephropathy to end stage renal disease. The best modality of treatment includes strict control over blood glucose levels and its evaluation at frequent intervals. Key Words: Diabetic Mellitus; Kidney Disease; Case Control Study; Nepal DOI: 10.3126/nje.v1i1.4108 Nepal Journal of Epidemiology 2010;1 (1):22-25